Negative Interpretation Biases Precede the Onset of Psychosis. Issue 4 (July 2019) - Yiend, Jenny; Allen, Paul; Lopez, Natalie D.; Falkenberg, Irina; Tseng, Huai-Hsuan; McGuire, Philip
Abstract: This study investigated whether a negative interpretation bias was present in people at high risk for psychosis. People with an At Risk Mental State (ARMS; n = 21), patients with First Episode Psychosis (FEP; n = 20), and healthy controls ( n = 20) performed three tasks, each of which was designed to measure interpretation bias. Both ARMS and FEP participants showed an attenuated positive bias compared to controls. These findings extend previous results investigating interpretation bias in psychosis by showing that interpretative biases are present before the onset of psychosis, and could therefore contribute to its development. Biased interpretation mechanisms could be a new target for clinical intervention in the early phase of psychosis. Highlights: Psychosis patients and people at high risk performed tests of interpretation bias. Both showed attenuated positive interpretation bias compared to healthy controls Maladaptive interpretative bias could contribute to psychosis development This cognitive mechanism could be targeted for early clinical intervention